Metafiction and Absurdity in Martin Amis’s London Fields (1989) - Aicha HOCINE (My University, 2017)
Western man’s inability to find meaning and the problematic issue of how individuals perceive reality have contributed to the rise of the postmodernist novel. This is due to the loss of values and the supreme authority of God while questioning God-novelist relationship. Accordingly, the postmodernist novel undermines the supreme authority of the author in favour of the reader's decision to construct or deconstruct the text. In this light, the main aim of this dissertation was to explore the underlying features which result from introducing a sense of absurdity with metafictional devices in Martin Amis’s London Fields (1989). To achieve this aim, the researcher adopted the descriptive and analytical approaches. This dissertation, then, considered what the absurdist themes have to offer to the postmodernist literature. I argued that the novel asserts the idea that chaos in literature is no longer distinct from the instability of individual’s life which point out the correlation between man’s seeking for purpose and man’s desire to find meaning in literary representation of the world.The dissertation was structured in three chapters.Eventually, it examined the need for employing the exhausted forms in postmodernist literature and illustrated the absurdist themes’ significance to highlight the playfulness of London Fields. It, also, pointed out the correlation between man’s search for purpose and his desire to find meaning in fiction and questioned the signifying interplay of self-reflexive elements in Amis’s novel.Most importantly, the study led to the conclusion that absurdity is a metafictional device in London Fields and Martin Amis could plainly explore the themes that create a sense of absurdity in his metafictional paradox. On the grounds of this conclusion, a number of recommendations were put forward to shed more light on the link between absurdity and the postmodernist features.
A Dissertation Submittedto the Department of English in Partial Fulfillment of the Requirements for the Degree of “Magister”in British, Commonwealth and American Studies